Chronic BPAF exposure differentially enhances fat deposition in mice fed normal or high-fat diets via lipid metabolism dysregulation - Lv, Ziquan; Xu, Xinyue; Tang, Zhi; Liang, Yin; Peng, Changfeng; Wu, Yuxuan; Sang, Dan; Jia, Guixuan; Hu, Xiaoxiao; Chen, Ying; Liu, Guangnan; Wang, Dan; et al. (Frontiers in Endocrinology, 2025)
BackgroundBisphenol AF (BPAF), an alternative to Bisphenol A (BPA), is increasingly utilized in various industrial applications, yet its toxicological profile remains incompletely understood. This study aims to investigate the impact of BPAF exposure on obesity and lipid metabolism in male mice subjected to either a normal chow diet (ND) or a high-fat diet (HFD).MethodsMice were exposed to BPAF at a concentration of 100 μg/kg every other day for five months under different dietary conditions, and body weight, rectal temperature, and food intake were monitored regularly. After the mice were sacrificed, the hepatic lipid metabolism was analyzed by measuring serum, hepatic lipids and performing hepatic metabolomics; energy metabolism was elucidated by assessing thermogenic pathways in brown adipose tissue (BAT) and factors affecting ingestion in the hypothalamus; the development and pathways of obesity were indicated by exploring lipogenesis and lipolysis pathways and fat accumulation in white adipose tissue (WAT).ResultsHistomorphometric analyses indicated that BPAF exposure induced drived fat deposition in white adipose tissue through adipocyte hypertrophy-mediated pathways in eWAT of ND and HFD mice, accompanied by weight gain in HFD mice. Energy metabolism analysis showed that BPAF exposure decreased resting body temperature and reduced thermogenic factor expression in BAT of ND and HFD mice, which may affect energy expenditure. Hepatic metabolomics analysis suggested that BPAF exposure interfered with hepatic lipid metabolism in ND and HFD mice, with elevated levels of hepatic triglycerides, total cholesterol, and free fatty acids in HFD mice. Transcript analysis revealed altered expression levels of genes regulating lipid metabolism in white adipose tissue of ND and HFD mice, with a down-regulation observed in p-HSL protein expression, indicative of a potential inhibition effects of BPAF on lipolysis signaling pathway.ConclusionChronic BPAF exposure differentially exacerbates fat deposition in mice fed normal or high-fat diets via affecting lipid metabolism. Given the widespread prevalence of obesity and the pervasive environmental presence of BPAF, our findings provide valuable insights into the metabolic toxicity of BPAF, thereby raise further concern on the safe utilization and precision prevention of this unique chemical.